Variability in thermal stress thresholds of corals across depths - Tavakoli-Kolour, Parviz; Sinniger, Frederic; Morita, Masaya; Nakamura, Takashi; Harii, Saki (Frontiers in Marine Science, 2023)
Mesophotic habitats are potential refugia for corals in the context of climate change. The seawater temperature in a mesophotic habitat is generally lower than in a shallow habitat. However, the susceptibility and threshold temperatures of mesophotic corals are not well understood. We compared 11 mesophotic and shallow species to understand their thermal stress thresholds using physiological parameters. Coral fragments were exposed to two thermal stress treatments, with temperatures set at 30°C and 31°C, and a low-temperature treatment set at 28 °C as the "no stress" condition for 14 days. We found that the threshold temperature of coral species at mesophotic depths is slightly lower or equal to that of corals in shallow depths. The results suggest that species in the mesophotic coral ecosystems can survive low (<4 degree heating weeks) thermal stress. However, mass bleaching and high mortality can be expected when temperatures rise above 4 degree heating weeks.